THE EFFECT OF USING INSTAGRAM'S SOCIAL MEDIA FEATURES ON INCREASING BUSINESS ORGANIZATIONS - Karina Nine Amalia; Tri Agustina Nugrahani (Jurnal Cakrawala Ilmiah, 2023)
Social media was created from two operating words - social and media. Social, in this context, means interaction between individuals who share the same interests, groups, or even communities. Media as the name suggests, is a medium, channel, or platform that enables the creation and exchange of user-generated content. Social media is less than two decades in existence but has become widely accepted. Building relationships and interactions is the main reason for the adoption of social media networks by individuals, however, organizations capitalize on the ubiquitous use of these sites and view them as platforms that directly interact with existing and new customers for their goods and services. One of the image-based social media that can act in the business process is Instagram. Instagram features that will be tested include hashtags in captions, live Instagram, drop questions and vote. One of the features, namely voting on snapgrams on Instagram, is a phase pattern. The use of this feature will provide a decision for business organizations in making decisions from various options available to improve organizational performance